Pengaruh Bimbingan Individu dalam Meningkatkan Hasil Belajar Matematika Siswa Kelas V di SD Negeri 3 Nyalian - Ni Luh Buda Resini; I Made Candiasa; Ida Bagus Putu Arnyana (Jurnal Riset Pendidikan Dasar (JRPD), 2024)
This research aims to determine the difference in mathematics learning outcomes before being given individual guidance and after being given individual guidance to class V students at SD Negeri 3 Nyalian Elementary School. The type of research carried out was quasi-experimental (Pre-Experimental Design), One-group pretest-posttest type. The subjects of this research were all Class V students at SDN 3 Nyalian, consisting of 10 students whose learning results were below the KKM. Data collection uses the test method. The results of the research show that there is an influence of individual guidance in improving students' Mathematics learning outcomes because the results of the significance value of the paired sample t-test are 0.001 < 0.05 and the N-gain test results score 0.73, which means that individual guidance is effective in improving students' Mathematics learning outcomes. The conclusion is that individual guidance is influential and effective in improving students' Mathematics learning outcomes.